The Impact of Education, Work Experience, and Incentives on Audit Quality: The Mediating Role of Organizational Commitment - Saputra, Hendri (UPI YPTK Journal of Business and Economics, 2025)
The object of this study is the employees of the Sungai Penuh City Inspectorate. The type of research used in this study is quantitative causality research, the data collection method is by distributing questionnaires. The analysis technique used is multiple linear regression analysis with the help of the smartPLS program. The sampling technique in this study used saturated samples by analyzing 80 respondents.Based on the results of the analysis, it can be concluded that education has a positive and significant effect on organizational commitment. Work experience has a positive and significant effect on organizational commitment. Incentives have a positive and significant effect on organizational commitment. Education has a positive and significant effect on audit quality. Work experience does not have a significant effect on audit quality. Incentives do not have a significant effect on audit quality. Organizational commitment has a significant effect on audit quality. Organizational commitment mediates the effect of education on audit quality. Organizational commitment mediates the effect of work experience on audit quality. Organizational commitment mediates the effect of incentives on audit quality.